PENGEMBANGAN INOVASI PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI LEMBAGA PENDIDIKAN FORMAL - Rafliyanto, Muhammad; Mukhlis, Fahrudin (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This research is motivated by the lack of competency of an Islamic religious educator who is less than optimal in providing learning innovations to students. Researchers found several problems faced by Islamic religious educators, namely not finding innovation in the teaching and learning process which makes students feel bored and less than optimal in understanding the material provided. The purpose of this study is to assist the role of educators by finding models in digital media-based PAI learning that can assist educators in carrying out the process of teaching and learning activities. Researchers in this research used qualitative methods through a library research. The results of this study resulted in four main points which were then developed in the form of a narrative, while the four points are attached, among others, 1.) relevant the values ​​of the Pancasila student profile to the PAI subject, 2.) maintaining the existence of the PAI subject, 3.) optimizing role of PAI educators, 4.) use of technology in PAI learning, 5.) develop learning innovations based on problem-solving.